Peran Baitul Mal wat Tamwil (BMT) Al-Istiqamah dalam Pengembangan Usaha Mikro di Kabupaten Enrekang: The Role of Baitul Mal wat Tamwil (BMT) Al-Istiqamah in the Development of Micro Enterprises in Enrekang Regency - Nur, Ermin (Dirasat Islamiah: Jurnal Kajian Keislaman, 2023)
This study examines the strategic role of Baitul Mal wat Tamwil (BMT) Al-Istiqamah in efforts to improve the micro-economy in Enrekang Regency and the supporting and inhibiting factors encountered in this effort. This type of research is qualitative, with managerial and Islamic economic approaches. Primary data sources are informants consisting of founders, administrators, members, and customers of BMT Al-Istiqamah, as well as the government of Enrekang Regency. Documents related to research as secondary data. Data collection techniques using observation, interviews, and documentation. Data analysis techniques use the stages of reduction, presentation, and drawing conclusions. The results showed that BMT Al-Istiqamah contributed to improving microeconomics in Enrekang. The roles played by BMT Al-Istiqamah are the empowerment of human resources and entrepreneurial spirit; improving microeconomic welfare; and preventing the public from practicing usury. Various factors supporting the success of BMT Al-Istiqamah are: strategic locations; the commitment of the founders, administrators, and members; high member savings participation; the high demand for microbusiness actors for BMT Al-Istiqamah; ease of obtaining capital assistance; and government support. The obstacles are the lack of human resources at BMT Al-Istiqamah, the lack of financial capital, the lack of technology utilization, and the number of customers who neglect to make deposit payments.